PELAKSANAAN EKSEKUSI PUTUSAN PENGADILAN HUBUNGAN INDUSTRIAL NOMOR 10/Pdt.Sus-PHI/2021/PNPbr - Haga Ray Prananta Tarigan; Rika Lestari; Rahmad Hendra (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
An inkracht decision is the process of final resolution of a dispute that has been decidedby the court. In the implementation of decision No: 10/Pdt.Sus-PHI/2021/PNPbr which wasimplemented voluntarily on May 12 2021, the payment made by the company was not inaccordance with the results of the decision which should have been IDR 48,622,000-, (FortyEight Million Six Hundred Twenty Two Thousand Rupiah), but it is lower, namely IDR.40,000,000, - (forty million rupiah). Therefore, the aim of writing this thesis is: first, to find outabout the implementation of decision No: 10/Pdt.Sus-PHI/2021/PNPbr. Second, to find outwhat are the obstacles to the execution process in the implementation of decision No:10/Pdt.Sus-PHI/2021/PNPbr.The research method in this thesis uses a type of sociological legal research, namelyresearch on the effectiveness of law in society. The nature of this thesis research isresearchdescriptivewhich systematically describes the facts and characteristics of the objectbeing studied accurately. The data collection technique in this research is the interview methodand literature review, then after the data is collected it is then analyzed to draw conclusions.From the research results it was found that the implementation of decision no.10/Pdt.Sus-PHI/2021/PNPbr carried out voluntarily by PT. Cipta Daya Sejati Luhur to EbietSiallagan by paying not in accordance with the district court's decision, the shortfall must stillbe paid for the sake of legal certainty of the decision to the plaintiff, the Pekanbaru districtcourt must recall the parties to carry out the voluntary execution of the court decision in thePekanbaru district court environment witnessed by the court in accordance with the laws andregulations in force in Indonesia, then Obstacles in implementing decision number No.10/Pdt.Sus-PHI/2021/PNPbr The first is that there are no statutory regulations governing thetime limit for implementing decisions voluntarily, disbursing money fromat PT. Create SublimeTrue Power It takes quite a long time for the losing party to carry out the decision not inaccordance with the verdict.Keywords: Implementation-execution-court-decision.